Jasmonate-Dependent Induction of Indole Glucosinolates in Arabidopsis by Culture Filtrates of the Nonspecific Pathogen Erwinia carotovora - Brader, Günter (American Society of Plant Physiologists, 2001)
Elicitors from the plant pathogen Erwinia carotovora trigger coordinate induction of the tryptophan (Trp) biosynthesis pathway and Trp oxidizing genes in Arabidopsis. To elucidate the biological role of such pathogen-induced activation we characterized the production of secondary defense metabolites such as camalexin and indole glucosinolates derived from precursors of this pathway. Elicitor induction was followed by a specific increase in 3-indolylmethylglucosinolate (IGS) content, but only a barely detectable accumulation of the indole-derived phytoalexin camalexin. The response is mediated by jasmonic acid as shown by lack of IGS induction in the jasmonate-insensitive mutant coi1-1. In accordance with this, methyl jasmonate was able to trigger IGS accumulation in Arabidopsis. In contrast, ethylene and salicylic acid seem to play a minor role in the response. They did not trigger alterations in IGS levels, and methyl jasmonate- or elicitor-induced IGS accumulation in NahG and ethylene-insensitive ein2-1 mutant plants was similar as in the wild type. The breakdown products of IGS and other glucosinolates were able to inhibit growth of E. carotovora. The results suggest that IGS is of importance in the defense against bacterial pathogens.